(untitled) (Revista Latino-Americana de Enfermagem, 2008)
This study aimed to identify variables associated to the consumption of benzodiazepine among workers of a private company in the VIII Region, Chile. This is a cross-sectional and correlative study. Study population: 40 employees of a private company. The instruments included a questionnaire on socio-demographic variables and a benzodiazepine questionnaire. There was no record of benzodiazepine consumption at the moment of the study. Twenty percent (20%) of the interviewees had already used benzodiazepine in the past, whereas, half of them (10%) in the last year. The bivariate analysis of the last year consumption of benzodiazepine with work hours variables showed no significant relation (p=0.073). No association was found between benzodiazepine consumption and socio-demographic variables among the study participants.